Right Vertebral Artery Intermittent Flow Reversal Due to Innominate Artery Dissection - Corrado Tagliati; Alessia Quaranta; Marco Fogante; Stefania Lamja; Alfonso Alberto Matarrese; Davide Battista; Giulio Cocco; Giuseppe Lanni; Alberto Rebonato; Fabiola Principi; Giulio Argalia; Antonio Corvino; et al. (Diagnostics, 2025)
Here, we describe a case of an asymptomatic 73-year-old female patient who suffered from type A acute aortic dissection with epiaortic arteries involvement and underwent surgical operation 9 years ago. A follow-up color Doppler ultrasound revealed a right vertebral artery intermittent flow reversal due to innominate artery dissection. To our knowledge, no previous studies have reported this intermittent flow reversal; therefore, supra-aortic trunks should be considered among the possible causes of vertebral artery flow reversal.